Technologies of Self-Wrapping: Female Chanters in the Fayḍa Tijāniyya Sufi Community in Senegal - Joseph Hill (Religions)
The prevalent conception in many Muslim communities globally that women’s visibility must be minimized or attenuated in the presence of unrelated men profoundly shapes Muslim women’s relationship to visibility. Many Muslim women participate in and influence their communities through forms of “wrapping”—a semiotic act that covers and protects yet also identifies and displays. The concept of “wrapping” encompasses “veiling” yet moves beyond clichés of invisible and silenced Muslim women. In the Fayḍa Tijāniyya Sufi community in Senegal, female Sufi chanters were until recently practically unknown, largely due to the perception that a woman’s voice—like her body and social presence—is ʿawra, or something to be cloaked and protected. Since around 2009, however, female chanters have proliferated, some becoming online superstars and acting as formally appointed spiritual guides (muqaddamas). These women largely embrace the notion of a woman’s voice and body as ʿawra, yet they adopt various social and material technologies as “wrappers” that mediate their chanting before large audiences. Female chanters exemplify the dialectic in the Sufi tradition—between the flexibility associated with transcendent reality (ḥaqīqa) and the limits associated with divine law (sharīʿa)—which facilitates yet constrains adaptation to changing historical conditions.